OPTIMALISASI PENGELOLAAN KEUANGAN PEMERINTAH KABUPATEN BULUKUMBA MELALUI PERAN PENGAWAS INTERNAL - Bahar, A. Nurbaeti; Risal, M. Chaerul; Hisbullah, Hisbullah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
Regional financial management is an inseparable part of the implementation of government affairs which becomes regional authority as a result of the autonomous handover of government affairs. This study aims to find out how the role of internal supervisors in optimizing the financial management of the Bulukumba Regency Government. This research is field research. Optimization of financial management of the local government of Bulukumba Regency is carried out through tax intensification, the use of finance with the principle of accountability, conducting guidance and supervision in revenue management, the use of technology-based information systems, implementing a reward and punishment system to the regional revenue management apparatus, collaborating with the legislature, as well as conducting expenditure efficiency and supervising expenditures that have been included in APBD.